Urbanisation alters the flow of energy through stream food webs. Issue 5 (8th June 2016) - Docile, Tatiana; Rosa, Daniela C. O.; Figueiró, Ronaldo; Nessimian, Jorge
Abstract: Anthropogenic changes in the aquatic environment can influence macroinvertebrate communities, interfering with species richness and diversity. Few studies have investigated the effect of urbanisation in streams using a food web approach. The aim of this study was to describe the food webs of aquatic macroinvertebrates in streams located in urban and preserved areas of the Atlantic Rainforest domain. Sampling was conducted in the state of Rio de Janeiro, Brazil, at 10 urban and 10 preserved streams during the dry season (August–September) of 2012. The streams were characterised with respect to their environmental conditions. Macroinvertebrates were sorted and identified in the laboratory and gut contents were examined. Trophic relationships were plotted in consumer–resource food webs and network properties were used to compare the two sets of streams. Food webs in urban streams had higher linkage density and connectance, but consumers had fewer items in their guts, which may indicate reduced flow of energy and more unstable food webs. The base of the food webs in each land‐use type were also quite different, with higher amounts of plant detritus in preserved streams and fine detritus in urban streams. This study shows that preserved areas offer better conditions for the development of macroinvertebrates, resulting in more stable trophic structures when compared with environments under higher anthropogenic influence.